Electro-active elastomer composites based on doped titanium dioxide1. Issue 7 (21st February 2015) - Kossi, Alaedine; Bossis, Georges; Persello, Jacques
<x xml:space="preserve">Abstract</x> The TiO2-Acac/PDMS elastomer conserves a high elastic modulus change (ΔG′) after cross-linking and achieves ΔG′ higher than 500 kPa for an applied electric field of 2 kV mm−1.